Patterns of bee and butterfly diversity in Southeast and Southern East Asian megacities / Sing Kong Wah - Sing, Kong Wah (2016)

(untitled)
I investigated bee diversity and human perceptions of bees in four megacities – Greater Bangkok, Klang Valley, Pearl River Delta, and Singapore-Iskandar Malaysia. I sampled bees and conducted questionnaires at three different site types in each megacity: a botanical garden, central business district and peripheral suburban areas. Overall, the mean species richness and abundance of bees were significantly higher in peripheral suburban areas than central business districts (p < 0.05). Urban residents were unlikely to have seen bees but agreed that bees have a right to exist in their natural environment. Residents who did notice and interact with bees, were more likely to have positive opinions towards the presence of bees in cities. Additionally, I examined the species diversity of butterflies in urban parks in two cities ─ the Federal Territory of Kuala Lumpur, Malaysia and Shenzhen, South China. I investigated the relationships between butterfly species richness and three park variables: i) park age, ii) park size and iii) distance from the central business district. I conducted standardized butterfly sampling across different microhabitat types at each park: i) groves, ii) hedges, iii) flowerbeds and iv) unmanaged areas. I recorded 572 butterflies belonging to 60 species in Kuala Lumpur‟s urban parks. Although species richness was positively correlated with park age and size and negatively correlated with distance from the central business district; the correlations were not statistically significant. The highest species richness was recorded in the unmanaged microhabitat. In Shenzhen, I collected 1933 butterflies belonging to 74 species. Butterfly species richness showed weak negative correlations with park age and distance from the central business district but the positive correlation with park size was statistically significant (p < 0.05). Among microhabitat types, highest species richness was recorded in unmanaged areas.